Physiological, hematological, and biochemical responses in Hararghe-highland lamb subjected to water salinity levels of Lake Basaka in a semiarid area of Ethiopia - Diriba Tulu; Mengistu Urge; Yesihak Yusuf Mummed (Heliyon, 2022)
The present study aimed to evaluate the effect of drinking salinity levels in Lake water on the growth performance, and physiological, and blood constituents of Hararghe-highland lambs. A total of 28 lambs (average IBW of 18 ± 1.18kg) were categorized into four levels of water salinity, namely freshwater (510 mg/l TDS), lake Basaka water (LBW; 2600mg TDS/L); lake Basaka water plus 100% TDS of LBW; 5200mg TDS/L) and lake Basaka water plus 200% TDS of LBW; 7900mg TDS/L). The current results suggest that increased total dissolved solid levels in lake water increase the water intake of lambs while not affecting IBW, FBW, AWG, and FCR. Additionally, drinking saline lake with increasing total dissolved solid levels increased rectal temperature and respiration rate and caused a significant (P < 0.05) change in the concentrations of glucose, albumin, urea, triglycerides, sodium, AST, and ALT. Some hematological variables and biochemical constituents like creatinine, total protein, cholesterol, chlorides, potassium, magnesium, and calcium showed no significant (P > 0.05) differences. In conclusion, Hararghe-highland lambs from Ethiopia could tolerate lake Basaka water with a high salt level (7952 mg/L TDS).